Morphometrical analysis, histology, and taxonomy of Thyroscyphus ramosus (Cnidaria, Hydrozoa) from the coast of Brazil - Shimabukuro, Vanessa; Marques, Antonio C. (Zootaxa, 2006)
The hydroid Thyroscyphus ramosus is redescribed based on optical and SEM observations of morphology and on histological studies. Colonies from several localities extending over a coastline distance of over 4,000 km in Brazil were studied to establish intraspecific variations using morphometrical parameters in a correspondence analysis. We conclude that differences noted in some populations were taxonomically insignificant, and related to non–historical factors such as microhabitat diversity.